2010
DOI: 10.1021/bi101316y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, Distributed Interactions of μ-Conotoxin PIIIA Associated with Broad Targeting among Voltage-Gated Sodium Channels

Abstract: The first μ-conotoxin studied, μCTX GIIIA, preferentially blocked voltage-gated skeletal muscle sodium channels, Na(v)1.4, while μCTX PIIIA was the first to show significant blocking action against neuronal voltage-gated sodium channels. PIIIA shares >60% sequence identity with the well-studied GIIIA, and both toxins preferentially block the skeletal muscle sodium channel isoform. Two important features of blocking by wild-type GIIIA are the toxin's high binding affinity and the completeness of block of a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 38 publications
8
40
0
Order By: Relevance
“…The basic residues of PIIIA (McArthur et al, 2011), and of other CTXs, play a vital role in toxin binding to the pore of voltage-gated sodium channels and in blocking current through the channel. Given the high sequence identity between GIIIA and PIIIA, most of the important basic residues are conserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The basic residues of PIIIA (McArthur et al, 2011), and of other CTXs, play a vital role in toxin binding to the pore of voltage-gated sodium channels and in blocking current through the channel. Given the high sequence identity between GIIIA and PIIIA, most of the important basic residues are conserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Currents were elicited with a 2-s prepulse to Ϫ140 mV to remove inactivation followed by a test pulse to Ϫ10 mV for 10 ms repeated every 5 s during toxin application and washout to record kinetics. Single-channel bilayer experiments using batrachotoxinmodified skeletal muscle Na v channel at steady state were carried out as described previously (McArthur et al, 2011a).…”
Section: Methodsmentioning
confidence: 99%
“…This residual single-channel current may be permitted by the absence of arginine and lysine residues in its N-terminal segment (residues 1-6), given that the PIIIA R12A derivative shows a small residual current similar to that for KIIIA (McArthur et al, 2011a). Even though KIIIA binds to the sodium-channel pore site 1, either tetrodotoxin or saxitoxin can bind simultaneously ), increasing the range of possible pharmacological actions of KIIIA by its use in combination with the smaller pore blockers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…174 With Arg 14 positioned in the permeation pathway, PIIIA causes steric and/or electrostatic occlusion of the channel pore. 175 Replacement of His 19 by Gln increases the selectivity of PIIIA for Na V 1.4 over Na V 1.2, 175 suggesting that His 19 , which is highly conserved among m-conotoxins, increases selectivity for the neuronal subtype. Interestingly, a recent study demonstrated that PIIIA isoforms with different cysteine connectivity (i.e., without changes in the primary structure) can be more potent blockers of Na V 1.4.…”
mentioning
confidence: 99%